INTERVENSI DUMBBELL LUNGES DAN CORE STABILITY EXERCISE LEBIH BAIK DARIPADA INTERVENSI ELASTIC BAND DAN CORE STABILITY EXERCISE TERHADAP PENINGKATAN KESEIMBANGAN DINAMIS PADA PEMAIN SKATEBOARD DENGAN KONDISI CHRONIC ANKLE INSTABILITY - Alit Kamayoga, I Dewa Gede; Adiputra, Nyoman; Indra Lesmana, Syahmirza; Tirtayasa, Ketut; Ngurah, Ida Bagus; Imron, M. Ali (Sport and Fitness Journal; Volume 5, No.3, 2017DO - 10.24843/spj.2017.v05.i03.p12, 2017)
Among skateboarders frequently faced with recurrent injury especially on ankle region. They seldom take attention to their injury and if the condition left untreated, it will turn into chronic ankle instability. This condition will disturb dynamic balance while playing skateboard. The purpose of this research is to find if dumbbell lunges intervention and core stability exercise are more effective than elastic band and core stability exercise for the improvement of dynamic balance. This experimental research using pre and post test two group design. Sample was taken with simple random sampling. Total of 24 samples were divided into 2 groups, each group contain 12 samples. Group I had dumbbell lunges intervention and core stability exercise while Group II had elastic band intervention and core stability exercise. The exercise was done 3 times per week for 6 weeks. Data was taken with measurement dynamic balance using modified bass test of dynamic balance before and after exercise to each group. The mean difference test increasement of dynamic balance with paired sample t-test results p value 0.001 (p<0.05) within treatment Group I and p value 0.001 (p<0.05) within treatment Group II. which mean there is significantly difference of increasing value dynamic balance before and after intervention within both group. Difference test before intervention in treatment Group I and Group II with independent t-test result p value 0.818 (p>0.05) in which there is no significant difference between groups before intervention. and difference test after intervention in treatment Group I and Group II with independent t-test shows significant difference with p value 0.001 (p<0.05). This study shows that dumbbell lunges intervention and core stability exercise result in better improvement of dynamic balance than elastic band intervention and core stability exercise among skateboarders.